Challenging comparison of stroke scales - Kavian Ghandehari (Journal of Research in Medical Sciences, 2013)
Stroke scales can be classified as clinicometric scales and functional impairment, handicap scales. All studies describing stroke scales were reviewed by internet searching engines with the final search performed on January 1, 2013. The following string of keywords was entered into search engines; stroke, scale, score and disability. Despite advantages of modified National Institute of Health Stroke Scale and Scandinavian stroke scale comparing to the NIHSS, including their simplification and less inter-rater variability; most of the stroke neurologists around the world continue using the NIHSS. The modified Rankin scale (mRS) and Barthel index (BI) are widely used functional impairment and disability scales. Distinction between grades of mRS is poorly defined. The Asian stroke disability scale is a simplified functional impairment, handicap scale which is as valid as mRS and BI. At the present time, the NIHSS, mRS and BI are routine stroke scales because physicians have used to work with these scales for more than two decades, although it could not be an acceptable reason. On the other side, results of previous stroke trials, which are the basis of stroke management guidelines are driven using these scales.